PROFIL LULUSAN PRODI PENDIDIKAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Roza, Cici Yoma; Faridah, Anni; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The aim of this research is 1. To see the study period and waiting time of the graduates, 2. The GPA, 3. To see the graduates’ jobs, 4. To see the suitability of their jobs, 5. To see their salary.The kind of this research is quantitative descriptive. The population is all graduates of Family Welfare Education Department in 2008 – 2012 amounted 268 persons. The samples is 40 persons using random sampling. The data process did by determining the percentage of respondents answers base on the aim of this research.The result shows that on average, the respondents have 5 years study period and 7 months waiting time. On average the respondents have 3.01 – 3.50 GPA. Most graduates work as the teachers in formal education institution, but some of the graduates are the entrepreneurs. The salary of the graduates is Rp 3.000.000 on average per month. Most of them said that the curriculum that they had in university is suitable with their jobs.Keywords : profile, graduates, family welfare department